A putrescine–anthracene conjugate : a paradigm for selective drug delivery - Palmer, Andrew; Abdul Ghani, Radiah; Kaur, Navneet; Phanstiel, Otto; Wallace, Heather (BJ Immediate Publication, Great Britain, 2009)
Increased polyamine concentrations play an important role in the development of cancer at all stages, from initiation through to maintenance of the transformed phenotype. One way cancer cells accumulate increased concentrations of polyamines is by increased uptake of preformed polyamines via their PTS(polyamine transport system). The PTS is promiscuous and will transport a range of polyamine-based molecules. Therefore it may be that cytotoxic drugs could be attached to polyamine vectors and targeted selectively to cancer cells by utilizing the PTS. The aim of the present study was to investigate the potential of Ant 4, a putrescine–anthracene conjugate, to target cytotoxic agents to human cancer cells as a paradigm for a novel method of selective drug delivery. Ant 4 induced cytotoxicity after only 24 h exposure. Apoptosis was the predominant type of cell death, with mechanistic studies revealing that oxidative stress and DNA damage may have a part to play. For the first time, uptake of Ant 4 via the PTS was demonstrated both directly and indirectly in human cell lines. In addition, Ant 4 significantly reduced putrescine uptake, demonstrating that this conjugate not only used the PTS, but also could successfully compete with its native polyamine for uptake. However, the most interesting finding was the intracellular depletion of the polyamine pools, providing an additional mode of toxicity for Ant 4 and the possibility that this molecule may act as a ‘double-edged sword’: preventing cell growth by delivery of the toxic moiety and by depletion of intracellular polyamine content.